Music during the Croatian war (1991 – 1995) - Rubić, Tihana (2005)
We try to analyse popular music from the period of the war in Croatia (1991- 1995) within the framework of its symbolic and strongly context-defined meaning. The domestic music production intensified a lot in the stated period of time with the purpose of raising morale and attempting 'spiritual mobilisation' (Bonifačić, 1995:73) via musical programmes and festivals that took place during the Homeland War in Croatia.